A sodium ion battery positive electrode material and preparation method thereof

By using a combination of polyanionic phosphate and carbon composite in the sodium ion battery positive electrode material, the X/Y ratio and structural performance of the material are optimized, and the problem of poor rate performance and cycle stability of the existing sodium ion battery positive electrode material is solved, and higher rate performance, cycle performance and capacity are achieved.

CN115986080BActive Publication Date: 2025-04-25SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211725247.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2025-04-25
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

The current sodium ion battery cathode materials have poor rate performance and cycle stability, making it difficult to meet the needs of large-scale production and cost-effectiveness.

Method used

The sodium ion battery positive electrode material is used that includes polyanionic phosphate and a carbon composite loaded on the polyanionic phosphate. The molecular formula of the polyanionic phosphate is NaXFeY(PO4)2P2O7, wherein, 3

Benefits of technology

It improves the transfer rate of sodium ions and significantly improves the rate performance, cycle performance and capacity of the material, making the battery perform better in terms of high magnification and long cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115986080B_ABST
    Figure CN115986080B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of sodium ion battery materials, and specifically provides a sodium ion battery positive electrode material and a preparation method thereof. The sodium ion battery positive electrode material comprises a polyanion phosphate and a carbon coating layer coated on the surface of the polyanion phosphate. The molecular formula of the polyanion phosphate is Na X Fe Y (PO4)2P2O7, wherein 3<X<4, 2<Y<3, and 1.25≤X / Y≤1.32. The positive electrode material has not only iron defects at the iron site, but also sodium vacancies at the sodium site. The combination of the two greatly improves the transmission rate of sodium ions, thereby improving the rate performance, cycle performance and capacity of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sodium ion battery materials, and in particular to a sodium ion battery positive electrode material and a preparation method thereof. Background Art

[0002] Compared with other types of sodium-ion battery cathode materials, polyanion-type sodium battery cathode materials have attracted widespread attention due to their higher electrode potential, stable structural framework, good thermal stability and fast sodium ion insertion and extraction kinetics. Among them, sodium iron-based polyanion compounds have great advantages in the competition for large-scale production, cost-effectiveness and environmentally friendly sodium-ion battery cathode materials due to the abundant and low-priced raw material iron and the simple material preparation process. In particular, Fe-based polyanion compounds have great advantages in the competition for large-scale production, cost-effectiveness and environmentally friendly sodium-ion battery cathode materials. 2+ / Fe 3+ The redox reaction of these materials involves more than one electron transfer during the charge and discharge process, which makes the materials usually have higher working voltage and discharge specific capacity, as well as higher energy density. Among them, the most prominent one is the sodium iron-based pyrophosphate material, which has a three-dimensional sodium ion diffusion channel in its structure and has excellent electrode kinetics. The Na 4-x Fe 2+x / 2 (P2O7)2, (2 / 3≤x≤7 / 8) material is considered to be a strong competitor as a positive electrode material for sodium ion batteries. When x=2 / 3, Na 3.32 Fe 2.34 (P2O7)2 has a theoretical capacity of 117.4 mAh / g, but the rate performance and cycle performance of this material are not very ideal. Therefore, other composite materials are needed to improve the rate performance and cycle performance of polyanion positive electrode materials. Summary of the invention

[0003] Therefore, the technical problem to be solved by the present invention is to overcome the defects of poor rate performance and cycle stability of the positive electrode material of sodium ion batteries in the prior art, thereby providing a positive electrode material and a preparation method thereof.

[0004] To this end, the present invention provides a sodium ion battery positive electrode material, including a polyanion phosphate and a carbon composite loaded on the polyanion phosphate, wherein the molecular formula of the polyanion phosphate is Na X Fe Y (PO4)2P2O7, wherein 3<X<4, 2<Y<3, and 1.25≤X / Y≤1.32.

[0005] The carbon composite can be loaded on the surface of the polyanionic phosphate or loaded inside the polyanionic phosphate.

[0006] Furthermore, the polyanion phosphate is selected from Na 3.718 Fe 2.885 (PO4)2(P2O7),Na 3.818 Fe 2.912 (PO4)2(P2O7) and Na 3.62 Fe 2.77 One or more of (PO4)2(P2O7).

[0007] Furthermore, the unit cell parameters of the sodium ion battery positive electrode material meet the following conditions: And / or, the XRD spectrum of the sodium ion battery positive electrode material expressed in 2θ angle has a characteristic peak at 11.09°±0.2°.

[0008] Furthermore, the peak area of ​​the characteristic peak (222) of the sodium ion battery positive electrode material and its half-peak width satisfy the relationship: 2<S / F<20, where S is the peak area of ​​the characteristic peak (222), and F is the half-peak width of the characteristic peak (222).

[0009] Preferably, 5≤S / F≤10.

[0010] Furthermore, the raw materials of the polyanion phosphate include materials containing sodium, iron and phosphorus elements and citric acid monohydrate; the raw materials of the carbon composite include an organic carbon source and an inorganic carbon source, preferably, the inorganic carbon source is selected from one or more of carbon nanotubes, graphene oxide, carbon black, acetylene black, and Ketjen black, and the organic carbon source is selected from one or more of glucose, sucrose, and lactose.

[0011] Furthermore, the material containing sodium, iron and phosphorus includes sodium salt containing phosphate, and also includes one or more of iron salt containing phosphate and iron salt not containing phosphate; or, the material containing sodium, iron and phosphorus includes sodium salt not containing phosphate and iron salt containing phosphate.

[0012] Furthermore, the sodium salt containing phosphoric acid is selected from one or more of sodium phosphate and sodium dihydrogen phosphate; the sodium salt not containing phosphoric acid is selected from one or more of sodium carbonate, disodium hydrogen phosphate and sodium bicarbonate; the iron salt containing phosphoric acid is iron phosphate, and the iron salt not containing phosphoric acid is selected from one or more of iron oxalate, iron acetate and iron sulfate.

[0013] Furthermore, based on the total mass of the raw materials of the sodium ion battery positive electrode material being 100%, the mass of the raw materials of the polyanion phosphate accounts for 90-99%.

[0014] The present invention also provides a method for preparing any of the above-mentioned positive electrode materials for sodium ion batteries, comprising mixing a material containing sodium, iron and phosphorus elements, citric acid monohydrate, a carbon source and water to prepare a mixed solution, and subjecting the mixed solution to ball milling, drying and calcining to obtain the positive electrode material for sodium ion batteries.

[0015] Further, the calcination is as follows: heating to 450-600° C. at a heating rate of 1-3° C. / min under nitrogen or inert gas, and calcining at 450-600° C. for 9-11 hours.

[0016] In certain preferred embodiments, a pulverizing step is further included between drying and calcining.

[0017] The technical solution of the present invention has the following advantages:

[0018] 1. The sodium ion battery positive electrode material provided by the present invention comprises a polyanion phosphate and a carbon coating layer coated on the surface of the polyanion phosphate, wherein the molecular formula of the polyanion phosphate is Na X Fe Y (PO4)2P2O7, wherein 3<X<4, 2<Y<3, and 1.25≤X / Y≤1.32. The positive electrode material has not only iron defects at the iron site, but also sodium vacancies at the sodium site. The combination of the two greatly improves the transmission rate of sodium ions, thereby improving the rate performance, cycle performance and capacity of the material.

[0019] 2. The sodium ion battery positive electrode material provided by the present invention, in certain preferred embodiments, controls 2<S / F<20 so that the material has better structural performance, the material is more stable, and thus the rate performance is better. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 1 and 2 are XRD patterns of the positive electrode materials obtained in Example 1 and Comparative Example 1. The upper pattern is the XRD pattern of Comparative Example 1, and the lower pattern is the XRD pattern of Example 1. DETAILED DESCRIPTION

[0022] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0023] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0024] Example 1 (Na 3.718 Fe 2.885 (PO4)2(P2O7)@C)

[0025] This embodiment provides a sodium ion battery positive electrode material, including a polyanion phosphate and a carbon composite, wherein the molecular formula of the polyanion phosphate is Na 3.718 Fe 2.885 (PO4)2(P2O7), X / Y=1.29, the raw materials of the positive electrode material of the sodium ion battery include trisodium phosphate, iron phosphate, citric acid monohydrate, carbon nanotubes and glucose, wherein the molar ratio of trisodium phosphate to iron phosphate is 1.2393:2.885, and the molar amount of citric acid monohydrate is one third of the molar amount of iron phosphate. Taking the total mass of the raw materials of the positive electrode material of the sodium ion battery as 100%, the mass of the carbon nanotubes accounts for 0.2% of the total mass, and the mass of the glucose accounts for 6% of the total mass.

[0026] The preparation method is as follows: trisodium phosphate, ferric phosphate, citric acid monohydrate, carbon nanotubes, and glucose are mixed, and pure water is added to prepare a solution with a solid content of 60%. The prepared solution is placed in a ball mill, and zirconium beads are added to the ball mill, with a ball-to-material mass ratio of 20:1, and then ball milled at 500rpm for 6 hours. The ball-milled material is dried at 120°C in a blast drying oven for 24 hours. The dried material is crushed using an ultracentrifugal grinder and sieved using a 400-mesh screen. The sieved material is calcined in a tubular furnace under a nitrogen atmosphere, with a calcination temperature of 500°C, a calcination time of 10 hours, and a heating rate of 2°C / min. The calcined material is sieved with 400 mesh to obtain a finished material.

[0027] Example 2 (Na 3.818 Fe 2.912 (PO4)2(P2O7)@C)

[0028] This embodiment provides a sodium ion battery positive electrode material, including a polyanion phosphate and a carbon composite, wherein the molecular formula of the polyanion phosphate is Na3.818 Fe 2.912 (PO4)2(P2O7), X / Y=1.31, the raw materials of the positive electrode material of the sodium ion battery include: sodium bicarbonate, iron phosphate, citric acid monohydrate, carbon black and sucrose, wherein the molar ratio of sodium bicarbonate to iron phosphate is 3.818:2.912, and the molar amount of citric acid monohydrate is one third of the molar amount of iron phosphate. Taking the total mass of the raw materials of the positive electrode material of the sodium ion battery as 100%, the mass of sucrose accounts for 5% of the total mass, and the mass of carbon black accounts for 0.1% of the total mass.

[0029] The preparation method is as follows: Sodium bicarbonate, ferric phosphate, citric acid monohydrate, carbon black and sucrose are mixed, and pure water is added to prepare a solution with a solid content of 65%. The prepared solution is placed in a ball mill, and zirconium beads are added to the ball mill, with a ball-to-material mass ratio of 20:1, and then ball milled at 500rpm for 6 hours. The ball-milled material is dried at 120°C in a blast drying oven for 24 hours. The dried material is crushed using an ultracentrifugal grinder and sieved using a 400-mesh screen. The sieved material is calcined in a tubular furnace under a nitrogen atmosphere, with a calcination temperature of 500°C, a calcination time of 10 hours, and a heating rate of 2°C / min. The calcined material is sieved with 400 mesh to obtain a finished material.

[0030] Example 3 (Na 3.62 Fe 2.77 (PO4)2(P2O7)@C)

[0031] This embodiment provides a sodium ion battery positive electrode material, including a polyanion phosphate and a carbon composite, wherein the molecular formula of the polyanion phosphate is Na 3.62 Fe 2.77 (PO4)2(P2O7), X / Y=1.31, the raw materials of the sodium ion battery positive electrode material include trisodium phosphate, iron phosphate, citric acid monohydrate, carbon nanotubes and glucose, wherein the molar ratio of trisodium phosphate to iron phosphate is 1.2067:2.770, the molar amount of citric acid monohydrate is one third of the molar amount of iron phosphate, and the total mass of the raw materials of the sodium ion battery positive electrode material is 100%, the mass of the carbon nanotubes accounts for 5% of the total mass, and the mass of the glucose accounts for 0.5% of the total mass.

[0032] The preparation method is as follows: trisodium phosphate, ferric phosphate, citric acid monohydrate, carbon nanotubes, and glucose are mixed, and pure water is added to prepare a solution with a solid content of 50%. The prepared solution is placed in a ball mill, and zirconium beads are added to the ball mill, with a ball-to-material mass ratio of 20:1, and then ball milled at 500rpm for 6 hours. The ball-milled material is dried at 120°C in a blast drying oven for 24 hours. The dried material is crushed using an ultracentrifugal grinder and sieved using a 400-mesh screen. The sieved material is calcined in a tubular furnace under a nitrogen atmosphere, with a calcination temperature of 500°C, a calcination time of 10 hours, and a heating rate of 2°C / min. The calcined material is sieved with 400 mesh to obtain a finished material.

[0033] Comparative Example 1 (Na4Fe3(PO4)2P2O7@C)

[0034] This comparative example provides a positive electrode material and a preparation method thereof, which are basically the same as Example 1, except that citric acid monohydrate is replaced by an equal molar amount of oxalic acid, and the molar ratio of the sodium element in trisodium phosphate and the iron element in ferric phosphate in the raw material is adjusted to 4:3, so that the molecular formula of the polyanion phosphate is: Na4Fe3(PO4)2P2O7, X / Y=1.33.

[0035] Comparative Example 2 (Na3Fe2(PO4)P2O7@C)

[0036] This comparative example provides a positive electrode material and a preparation method thereof, which are basically the same as Example 1, except that citric acid monohydrate is replaced by an equal molar amount of oxalic acid, and the molar ratio of the sodium element in trisodium phosphate and the iron element in ferric phosphate in the raw material is adjusted to 3:2, so that the molecular formula of the polyanion phosphate is: Na3Fe2(PO4)P2O7, X / Y=1.50.

[0037] Comparative Example 3 (Na 3.32 Fe 2.34 (P2O7)2@C)

[0038] This comparative example provides a positive electrode material and a preparation method thereof, which are basically the same as those in Example 1, except that citric acid monohydrate is replaced by oxalic acid, the molar ratio of oxalic acid to ferric phosphate is the same, and the molar ratio of sodium element in trisodium phosphate and iron element in ferric phosphate in the raw material is adjusted to 3.32:2.34, so that the molecular formula of the polyanion phosphate is: Na 3.32 Fe 2.34 (P2O7)2, X / Y=1.42.

[0039] Comparative Example 4 (Na4Fe 2.89 (PO4)2(P2O7)@C)

[0040] This comparative example provides a positive electrode material and a preparation method thereof, which is basically the same as Example 1, except that the molar ratio of sodium phosphate to iron phosphate is adjusted to 1.333:2.89, so that the molecular formula of the polyanion phosphate is: Na4Fe 2.89 (PO4)2(P2O7), X / Y=1.38.

[0041] ICP test results of the samples in Experimental Example 1

[0042] ICP element analysis and XRD analysis were performed on the positive electrode materials of each embodiment and comparative example, and the results are shown in the table below.

[0043] Table 1 Mass content of each element (%) Test

[0044]

[0045] ICP elemental analysis confirmed that the chemical formula of the polyanionic phosphate contained in the positive electrode material of each example and comparative example was as described in each example and comparative example.

[0046] Experimental Example 2 Electrical properties of positive electrode materials

[0047] The positive electrode materials prepared in the embodiments and comparative examples were used to assemble button cells in the following manner: the positive electrode material, conductive carbon black and binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 90:5:5, N-methylpyrrolidone (NMP) was used as a solvent, a slurry was prepared, and the slurry was evenly coated on an aluminum foil. After drying, the slurry was compacted to a compacted density of 2.0 g / cm 3 , surface density is 9g / cm 2 , and dried at 120℃ in vacuum for 12h to obtain the positive electrode. The negative electrode uses a metal lithium sheet, the separator is a polypropylene porous membrane, and the electrolyte is 1 mol / L NaPF6 / EC+DEC+DMC (EC:DEC:DMC=1:1:1 volume ratio).

[0048] Initial specific capacity test conditions: 0.2C, voltage range 1.5V-4.05V test; Note: 1C = 129mA / g;

[0049] Rate performance test conditions: 0.2C test for 5 weeks, 10C test for 50 weeks, 0.2C test for 5 weeks, voltage range is 1.5V-4.05V, see the table below.

[0050] Cycle performance test conditions: 2C test for 300 cycles, voltage range is 1.5V-4.05V.

[0051] Table 2 Performance parameters of positive electrode materials

[0052]

[0053] It can be seen from the table that the polyanion phosphate in the sodium ion battery positive electrode material of the present invention has both iron defects and sodium defects, and has better performance, not only higher capacity and rate performance, but also significantly improved cycle performance.

[0054] XRD pattern of the sample of Example 3

[0055] The positive electrode material of Example 1 was tested by X-ray diffractometer, and it was a monoclinic phase structure with a space group of Pn21a and the following unit cell parameters: The unit cell expansion rate is 2.12%. The XRD spectrum of the positive electrode material includes the following diffraction peaks shown at 2θ angles:

[0056] Table 3 XRD spectrum data of the positive electrode material of Example 1

[0057] Peak number Angle 2θ(°) Relative strength (%) 1 10.67 10.4 2 11.09 7.89 3 15.92 12.87 4 16.69 13.17 5 19.33 7.13 6 23.91 6.28 7 25.42 5.35 8 27.30 6.09 9 32.14 10.75 10 34.12 9.75 11 36.89 5.63 12 42.68 4.69

[0058] Table 4 XRD spectrum data of the positive electrode material of Comparative Example 1

[0059] Peak number Angle (2θ) Relative strength (%) 1 10.7 9.2 2 15.91 11.37 3 16.72 11.83 4 19.36 9.08 5 23.89 8.02 6 25.45 7.80 7 27.29 8.43 8 32.13 9.86 9 34.12 9.12 10 36.90 7.92 11 42.69 7.38

[0060] As can be seen from the above table, the XRD spectrum of the polyanion phosphate in the positive electrode material of the sodium ion battery of the present invention has both iron defects and sodium defects, and there is a characteristic peak at about 11.09°, producing different crystal forms. The battery using the positive electrode material not only has higher capacity and rate performance, but also has significantly improved cycle performance.

[0061] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A sodium ion battery positive electrode material, characterized in that: The invention comprises a polyanionic phosphate and a carbon composite loaded on the polyanionic phosphate, wherein the molecular formula of the polyanionic phosphate is Na X Fe Y (PO4)2P2O7, wherein 3<X<4, 2<Y<3, and 1.25≤X / Y≤1.32; the peak area of ​​the characteristic peak (222) of the sodium ion battery positive electrode material and its half-peak width satisfy the relationship: 2<S / F<20, wherein S is the peak area of ​​the characteristic peak (222), and F is the half-peak width of the characteristic peak (222).

2. The sodium ion battery positive electrode material according to claim 1, characterized in that The polyanionic phosphate is selected from Na 3.718 Fe 2.885 (PO4)2(P2O7),Na 3.818 Fe 2.912 (PO4)2(P2O7) and Na 3.62 Fe 2.77 One or more of (PO4)2(P2O7).

3. The sodium ion battery positive electrode material according to claim 1 or 2, characterized in that The unit cell parameters of the sodium ion battery positive electrode material meet the following conditions: And / or, the XRD spectrum of the sodium ion battery positive electrode material expressed in 2θ angle has a characteristic peak at 11.09°±0.2°.

4. The sodium ion battery positive electrode material according to claim 1 or 2, characterized in that The peak area of ​​the characteristic peak (222) of the sodium ion battery positive electrode material and its half-peak width satisfy the relationship: 5≤S / F≤10.

5. The sodium ion battery positive electrode material according to claim 1 or 2, characterized in that: The raw materials of the polyanion phosphate include materials containing sodium, iron and phosphorus elements and citric acid monohydrate; the raw materials of the carbon complex include organic carbon sources and inorganic carbon sources.

6. The sodium ion battery positive electrode material according to claim 5, characterized in that The inorganic carbon source is selected from one or more of carbon nanotubes, graphene oxide, and carbon black, and the organic carbon source is selected from one or more of glucose, sucrose, and lactose.

7. The sodium ion battery positive electrode material according to claim 5, characterized in that The inorganic carbon source is selected from one or more of acetylene black and Ketjen black.

8. The sodium ion battery positive electrode material according to claim 5, characterized in that The material containing sodium, iron and phosphorus includes sodium salt containing phosphate, and also includes one or more of iron salt containing phosphate and iron salt not containing phosphate; or, the material containing sodium, iron and phosphorus includes sodium salt not containing phosphate and iron salt containing phosphate.

9. The sodium ion battery positive electrode material according to claim 8, characterized in that The sodium salt containing phosphoric acid is selected from one or more of sodium phosphate and sodium dihydrogen phosphate; the sodium salt not containing phosphoric acid is selected from one or more of sodium carbonate and sodium bicarbonate; the iron salt containing phosphoric acid is iron phosphate, and the iron salt not containing phosphoric acid is selected from one or more of iron oxalate, iron acetate and iron sulfate.

10. The sodium ion battery positive electrode material according to claim 1 or 2, characterized in that: Taking the total mass of raw materials of the sodium ion battery positive electrode material as 100%, the mass of the raw materials of the polyanion phosphate accounts for 90-99%.

11. A method for preparing the positive electrode material for a sodium ion battery according to any one of claims 1 to 10, characterized in that: The method comprises the steps of mixing materials containing sodium, iron and phosphorus elements, citric acid monohydrate, a carbon source and water to prepare a mixed solution, and subjecting the mixed solution to ball milling, drying and calcining to obtain a positive electrode material for a sodium ion battery.

12. The method for preparing a positive electrode material for a sodium ion battery according to claim 11, characterized in that: The calcination is as follows: heating to 450-600° C. at a heating rate of 1-3° C. / min under nitrogen or inert gas, and calcining at 450-600° C. for 9-11 hours.

Citation Information

Patent Citations

  • Ferric pyrophosphate-based sodium ion battery positive electrode composite material and preparation method thereof

    CN114050244A